CTNI-30. LOGGIC/FIREFLY-2: A PHASE 3, RANDOMIZED TRIAL OF TOVORAFENIB VS. CHEMOTHERAPY IN PEDIATRIC PATIENTS WITH NEWLY DIAGNOSED LOW-GRADE GLIOMA HARBORING AN ACTIVATING RAF ALTERATION. (14th November 2022) - van Tilburg, Cornelis; Jones, David T; Schmidt, Rene; Avula, Shivaram; van Meeteren, Antoinette Schouten-; Sehested, Astrid; Opocher, Enrico; Driever, Pablo Hernáiz; Witt, Ruth; Ziegler, David; Blackman, Samuel; Zhao, Xin; et al.
Abstract: BACKGROUND: Genomic alterations and dysregulation of RAF are the main oncogenic driver in almost all pediatric low-grade gliomas (pLGGs). About 50%‒60% of pLGGs harbor KIAA1549-BRAF fusion and 5%‒15% BRAF V600E mutation. No targeted therapy has received regulatory approval for either relapsed or newly diagnosed pLGG to date. Tovorafenib is an investigational, oral, selective, CNS-penetrant, small molecule, type II panRAF inhibitor. The registrational, phase 2 FIREFLY-1 (NCT04775485) study with tovorafenib in pediatric patients with recurrent/progressive LGG is currently ongoing. METHODS: LOGGIC/FIREFLY-2 (EudraCT 2022-001363-27) is a registrational, randomized, multicenter, global ( 100 sites across Australia, Canada, Egypt, Europe, New Zealand, Singapore, South Korea, Taiwan, and USA), phase 3 trial evaluating the efficacy, safety, and tolerability of tovorafenib vs. standard of care (SoC) chemotherapy in patients < 25 years old with LGG harboring a RAF-alteration and requiring first-line systemic therapy. Approximately 400 patients will be randomized 1:1 to receive oral tovorafenib, 420 mg/m 2 ( ≤ 600 mg) weekly (tablet or liquid suspension for 26, 28-day cycles), or an investigator's choice of SoC chemotherapy: COG-V/C regimen (60 weeks), SIOPe-LGG-V/C (81 weeks) regimen, or single-agent vinblastine (70 weeks). After completing 26 cycles tovorafenib, patients may continue tovorafenib or opt to enter a drug holiday at any point. Patients who progress in the SoC arm may receive tovorafenib. Patients who progress after stopping tovorafenib may be re-challenged. Primary endpoint is ORR based on RANO criteria, as determined by an independent radiology committee. Key secondary endpoints are progression-free survival and duration of response per RANO criteria, and ORR per RAPNO criteria. Other secondary endpoints include changes in neurological and visual function, and safety and tolerability. Exploratory objectives include quality of life and health utilization measures, molecular biomarker evaluation for treatment response and resistance, efficacy of tovorafenib after progression on chemotherapy and retreatment upon progression during drug holiday.